Seismic Vulnerability Analysis Using the Horizontal to Vertical Spectral Ratio (HVSR) Method on the West Palu Bay Coastline - Amirudin; Madrinovella, Iktri; Sofian (UIR PRESS, 2023)
This research was carried out to make a map of the dominant frequency (f0), amplification factor (A0), seismic susceptibility index (Kg), Vs30, Sediment Layer Thickness (H) and Peak ground acceleration (PGA). Microtremor measurements were carried out with a three-component seismometer of the TDL-303S type as many as 27 measurement points. The data was analyzed by the Horizontal to Vertical Spectral Ratio (HVSR) method. The PGA calculation was carried out using the Kanai equation with a reference to the Palu-Donggala earthquake on September 28, 2018. The results showed that the distribution of the dominant frequency value (f0) ranged from 0.4149 Hz-0.8869 Hz, the soil amplification factor (A0) ranged from 2,199–4,884, the seismic vulnerability index (Kg) ranged from 8.79 s2/cm-41.41 s2/cm, the shear wave velocity to a depth of 30 meters ( Vs30) ranged from Vs30 197.7 m/s-320.2 m/s , the thickness of the sedimentary layer ranges from 260.3 m-291.1 m and the peak ground acceleration (PGA) of Kanai ranges from 137.3 gal – 234.2 gal by using Mw 7.4 earthquakes with an intensity scale (MMI) VI to VII. The coastal area of West Palu bay has an intermediate seismic vulnerability II to a high seismic vulnerability IV so that it will be vulnerable in the event of an earthquake disaster. Areas that have a very high vulnerability index are in the upper western and easternmost regions while those with a lower level tend to have a lower vulnerability index value.